Development Of Cycle Counting Monitoring Dashboard With Buffer Time Management For Cocoa Company - Eriko Mahtamtama; Ari Yanuar Ridwan; Budi Santosa (eProceedings of Engineering, 2018)
Abstract— PT XYZ is a cocoa manufacturing company that produces 4 types of finished goods: Cocoa Butter, Cocoa Powder, Cocoa Mass, and Cocoa Cake. As one of the few company that produced this types of goods in a large scale in Indonesia, PT XYZ has to meet a high demand every day. Warehouse managers need a reliable inventory monitoring dashboard that could help them monitors the item inside their warehouse. This research presents a case study of inventory control in cocoa company. This research aims for Inventory monitoring dashboard that could perform cycle counting process which also implementing a specific concept of Theory of Constraints (TOC) which is Buffer Time Management. This concept applying buffers on a certain period of time for each of items inside the warehouse, the monitoring dashboard then could alarm the user the condition of each items in the warehouse with color indicators. The user then can schedule the ‘alarmed’ items into the Stock capture sheets where the item will be counted when the company is performing cycle counting. By using this application it is expected that the inventory accuracy in PT XYZ may improve. Keywords— Cycle Counting, Buffer Time Management, Cocoa, Monitoring, Dashboard.